(untitled) (Research, Society and Development, 2021)
The evaluation of the user experience using a software directly affects its quality. The System Usability Scale measures the end user’s experience with the system, which presents contradictory issues. The objective of this article is to demonstrate a deepening of those contradictions, using the Evidential Annotated Paraconsistent Logic Eτ, with the application of a survey for eleven professionals who evaluated a system. A comparison of the results of the above scale was performed with the Para-analyzer algorithm, using the pair (μ, λ), assigning the even questions to μ and the odd questions to λ. The first result showed a positive assessment of usability, with the System Usability Scale (76.59). The second result, performed with the Para-analyzer, presented the global average (0.75, 0.25), which indicates a similarity with the first, highlighting two contradictory items. The evaluation improved the usability analysis, as respondents agreed on nine usability characteristics. However, there was a divergence in one item, as five respondents rated two questions with high values, presenting a contradiction in the assessment. This result may show a perception failure in the instrument’s semantics, which could indicate a need for training of participants before the beginning of the process. The main contribution of this research was to evaluate the usability of a software in conjunction with the Para-analyzer, enabling a more detailed analysis, as it works with the pair (μ, λ), being possible to evaluate the results in two dimensions.